Social assistance receipt and its importance for combating poverty in urban China - Björn Gustafsson; Deng Quheng (Institute for the Study of Labor (IZA), 2007)
Since the second half of the 1990s economic restructuring in urban China has led to widespread joblessness and income insecurity. The rapid expansion of the system of social assistance, Di Bao, can be understood from this perspective. Using a survey covering large parts of urban China in 2002, we investigate factors affecting receipt and how receipt affects urban poverty. Results from estimating probability models indicate that social assistance receipt is strongly linked to joblessness among household members, the household's expenditure burden, as well as the lack of financial assets. Further, a long education of the household head and membership in the Communist Party reduces the probability of receiving social assistance while having been sent to rural China during the Cultural Revolution increases it. For some types of households, receipt of Di Bao differs greatly across cities in China. The social assistance payments appear strongly targeted to the poor. However, as the Di Bao payments typically are small and many of the urban poor are not receivers, much urban poverty remains.
urn:nbn:de:101:1-20080402161
Keywords: 330; Sozialhilfe; Armutspolitik; Ländliche Armut; China